2009
DOI: 10.1109/tpds.2008.256
|View full text |Cite
|
Sign up to set email alerts
|

How to Effectively Use Multiple Channels in Wireless Mesh Networks

Abstract: Abstract-Operating on a frequency band occupying several nonoverlapping channels, IEEE 802.11 is now widely used in Wireless Mesh Networks (WMNs). Many multichannel MAC protocols are proposed to improve the spatial reuse in the network under the assumption that the transmissions on nonoverlapping channels do not interfere with each other. Some joint routing and channel assignment algorithms are also designed to increase the network throughput based on the premise that we can switch between different channels f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…According to [51], the switching delay in 802.11a is around 328 microseconds, which is equal to the time of transmission of 1024 byte in a rate of 25 Mbps using the same technology. Furthermore, Li et al [52] show that this latency can rise, up to scale of seconds due to the effect of upper layer protocols. The authors in [53] presented an experimental study on the interruption associated with channel switching, which is in order of 10 seconds with the use of OLSR protocol due to fast link failure update in channel switching.…”
Section: Problem Formulation 31 Re-configuration Problem Descriptionmentioning
confidence: 99%
“…According to [51], the switching delay in 802.11a is around 328 microseconds, which is equal to the time of transmission of 1024 byte in a rate of 25 Mbps using the same technology. Furthermore, Li et al [52] show that this latency can rise, up to scale of seconds due to the effect of upper layer protocols. The authors in [53] presented an experimental study on the interruption associated with channel switching, which is in order of 10 seconds with the use of OLSR protocol due to fast link failure update in channel switching.…”
Section: Problem Formulation 31 Re-configuration Problem Descriptionmentioning
confidence: 99%
“…Therefore, we ſx the minimum time period between reconſgurations (α) to 5 minutes. As studies conducted in [22] show, channel reconſguration takes time in the order of seconds though the channel switching of the router radios may be of the order of milliseconds. Hence we assume β to take value of 3 secs.…”
Section: A Description Of Real Trafſc Tracesmentioning
confidence: 99%
“…If we use the optimal CA for every traffic demand in the network, without considering the current state of the network, it will lead to lot of reconfigurations and will heavily disrupt the ongoing traffic in the network. In [11], the authors have shown that though the channel switching time of the interface cards are in the order of micro seconds, the average traffic disruption time due to channel reconfiguration is in the order of seconds. If these reconfigurations happen frequently, the loss of packets and under utilization of the network will make WMNs very unreliable.…”
Section: Introductionmentioning
confidence: 99%